The Influence of DANA E-Wallet's Ease of Use on User Interest (Case Study of Private University Students in Tasikmalaya City) - Wulandari, Saripah Dwi; Abdillah, Wildan Army; Andriati, Yumi Sri (JURNAL BISNIS STRATEGI, 2024)
This research aims to determine the influence of DANA e-wallet’s ease of use on user interest among private university students in Tasikmalaya City. This study employs a quantitative method, using both primary and secondary data. Data collection was conducted through surveys/questionnaires. The population in this study comprises private university students in Tasikmalaya City, totaling 18,173 individuals, with sample selection through probability sampling. The sample size for this study is 100 people. The data analysis techniques used include descriptive analysis and verification analysis (simple linear regression analysis, coefficient of determination test, and t-test). The results show that the ease of use of the DANA e-wallet has a positive and significant influence on user interest, with a t-table value of 1.984 < t-count 4.817 and a significance value of 0.000 < 0.05. The contribution of DANA e-wallet’s ease of use to user interest is 19.1%, while the remaining 81.9% is influenced by other variables not included in this study. This means that the higher the ease of use of the DANA e-wallet, the greater the increase in user interest.